(untitled) (Práxis Educativa, 2022)
This article presents the results of a research that sought to discuss issues related to black teacher authority. The study sought to understand the authority of the teacher and relate it to the figure of the black teacher, in order to identify if they suffer any kind of depreciation or prejudice due to their color. We discuss, based on Aquino (2014) and Freire (1988), among others, the concept of authority, and on Domingues (2005) and Farias (2019), among others, blackness and structural racism. The research subjects were 10 black teachers and 10 students of the 5th grade of Elementary School from a school in the Municipal Network of Criciúma, Santa Catarina, Brazil. In the research, with a qualitative approach, a questionnaire was used as data collection. From the research, we came to the conclusion that the researched students demonstrated that they have in the figure of the teacher the authoritative reference, without distinction of color. However, 8 teachers claim that they feel their authority diminished and threatened. Keywords: Black teacher. Students. Authority.